A Randomized, Controlled Trial of Resistance Training Added to Caloric Restriction Plus Aerobic Exercise Training in Obese Heart Failure With Preserved Ejection Fraction. (31st October 2022) - Brubaker, Peter H.; Nicklas, Barbara J.; Houston, Denise K.; Hundley, W. Gregory; Chen, Haiying; Molina, Anthony J.A.; Lyles, W. Mary; Nelson, Benjamin; Upadhya, Bharathi; Newland, Russell; Kitzman, Dalane W.
Abstract : Background: We have shown that combined caloric restriction (CR) and aerobic exercise training (AT) improve peak exercise O2 consumption (VO2peak ), and quality-of-life in older patients with obese heart failure with preserved ejection fraction. However, ≈35% of weight lost during CR+AT was skeletal muscle mass. We examined whether addition of resistance training (RT) to CR+AT would reduce skeletal muscle loss and further improve outcomes. Methods: This study is a randomized, controlled, single-blind, 20-week trial of RT+CR+AT versus CR+AT in 88 patients with chronic heart failure with preserved ejection fraction and body mass index (BMI) ≥28 kg/m 2 . Outcomes at 20 weeks included the primary outcome (VO2peak ); MRI and dual X-ray absorptiometry; leg muscle strength and quality (leg strength ÷ leg skeletal muscle area); and Kansas City Cardiomyopathy Questionnaire. Results: Seventy-seven participants completed the trial. RT+CR+AT and CR+AT produced nonsignificant differences in weight loss: mean (95% CI): –8 (–9, –7) versus –9 (–11, –8; P =0.21). RT+CR+AT and CR+AT had non-significantly differences in the reduction of body fat [–6.5 (–7.2, –5.8) versus –7.4 (–8.1, –6.7) kg] and skeletal muscle [–2.1 (–2.7, –1.5) versus –2.1 (–2.7, –1.4) kg] ( P =0.20 and 0.23, respectively). RT+CR+AT produced significantly greater increases in leg muscle strength [4.9 (0.7, 9.0) versus –1.1 (–5.5, 3.2) Nm, P =0.05] and leg muscle quality [0.07 (0.03, 0.11) versus 0.02 (–0.02, 0.06) Nm/cm 2, P =0.04]. Both RT+CR+AT and CR+AT produced significant improvements in VO2peak [108 (958, 157) versus 80 (30, 130) mL/min; P =0.001 and 0.002, respectively], and Kansas City Cardiomyopathy Questionnaire score [17 (12, 22) versus 23 (17, 28); P =0.001 for both], with no significant between-group differences. Both RT+CR+AT and CR+AT significantly reduced LV mass and arterial stiffness. There were no study-related serious adverse events. Conclusions: In older obese heart failure with preserved ejection fraction patients, CR+AT produces large improvements in VO2peak and quality-of-life. Adding RT to CR+AT increased leg strength and muscle quality without attenuating skeletal muscle loss or further increasing VO2peak or quality-of-life. Registration: URL: https://ClincalTrials.gov ; Unique identifier: NCT02636439.